Pancreatic β-cells package double C2-like domain beta protein into extracellular vesicles via tandem C2 domains - Esparza, Diana; Lima, Carinna; Abuelreich, Sarah; Ghaeli, Ima; Hwang, Jinhee; Oh, Eunjin; Lenz, Ayelet; Gu, Angel; Jiang, Nan; Kandeel, Fouad; Thurmond, Debbie C.; Jovanovic-Talisman, Tijana (Frontiers in Endocrinology, 2024)
Introduction: Double C2-like domain beta (DOC2B) is a vesicle priming protein critical for glucose-stimulated insulin secretion in β-cells. Individuals with type 1 diabetes have lower levels of DOC2B in their residual functional β-cell mass and platelets, a phenotype also observed in a mouse model of T1D diabetic mice. Thus, DOC2B levels could provide important information on β-cell dys(function). Objective: Our objective was to evaluate the DOC2B secretome of β-cells. In addition to soluble extracellular protein, we assessed DOC2B localized within membrane-delimited nanoparticles - extracellular vesicles (EVs). Moreover, in rat clonal β-cells, we probed domains required for DOC2B sorting into EVs. Method: Using Single Extracellular VEsicle Nanoscopy, we quantified EVs derived from clonal βcells (human EndoC-βH1, rat INS-1 832/13, and mouse MIN6); two other cell types known to regulate glucose homeostasis and functionally utilize DOC2B (skeletal muscle rat myotube L6-GLUT4myc and human neuronal-like SH-SY5Y cells); and human islets sourced from individuals with no diabetes (ND). EVs derived from ND human plasma, ND human islets, and cell lines were isolated with either size exclusion chromatography or differential centrifugation. Isolated EVs were comprehensively characterized using dotblots, transmission electron microscopy, nanoparticle tracking analysis, and immunoblotting. Results: DOC2B was present within EVs derived from ND human plasma, ND human islets, and INS-1 832/13 β-cells. Compared to neuronal-like SH-SY5Y and L6-GLUT4myc myotubes, clonal β-cells (EndoC-βH1, INS-1 832/13, and MIN6) produced significantly more EVs. DOC2B levels in EVs (over whole cell lysates) were higher in INS-1 832/13 β-cells compared to L6-GLUT4myc myotubes; SH-SY5Y neuronal-like cells did not release appreciable DOC2B. Mechanistically, we show that DOC2B was localized to the EV lumen; the tandem C2 domains were sufficient to confer sorting to INS-1 832/13 β-cell EVs. Discussion: Clonal β-cells and ND human islets produce abundant EVs. In cell culture, appreciable DOC2B can be packaged into EVs, and a small fraction is excreted as a soluble protein. While DOC2B-laden EVs and soluble protein are present in ND plasma, further studies will be necessary to determine if DOC2B originating from β-cells significantly contributes to the plasma secretome.